2017
DOI: 10.1093/nar/gkx839
|View full text |Cite
|
Sign up to set email alerts
|

Role of free DNA ends and protospacer adjacent motifs for CRISPR DNA uptake in Pyrococcus furiosus

Abstract: To acquire CRISPR–Cas immunity against invasive mobile genetic elements, prokaryotes must first integrate fragments of foreign DNA into their genomic CRISPR arrays for use in future invader silencing. Here, we found that the hyperthermophilic archaeaon, Pyrococcus furiosus, actively incorporates DNA fragments (spacers) from both plasmid (foreign) and host genome (self) sequences into its seven CRISPR loci. The majority of new spacers were derived from DNA immediately downstream from a 5′-CCN-3′ protospacer adj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 60 publications
6
45
2
Order By: Relevance
“…The previous study used BL-21AI strain ( E. coli B) while we used E. coli K-12, which could be the reason for the observed difference. Another study ( 23 ) reported that P. furiosus cells acquired 96–99% of the unique spacers from the chromosome compared to 1–4% of new spacers derived from a plasmid expressing Cas proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The previous study used BL-21AI strain ( E. coli B) while we used E. coli K-12, which could be the reason for the observed difference. Another study ( 23 ) reported that P. furiosus cells acquired 96–99% of the unique spacers from the chromosome compared to 1–4% of new spacers derived from a plasmid expressing Cas proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of such selections include obtaining colonies of BIMs (bacteriophage insensitive mutants) ( Figure 1A) [4, 21,22,31,32] or PIMs ( plasmid interfering mutants) ( Figure 1B) [30,31,33]. These methods are cheap and do not require genetic manipulation of cells under study but they are biased towards interference-proficient spacers acquired from MGEs and thus cannot be used to detect spacers that do not lead to interference against MGEs or lead to self-interference due to acquisition of a spacer from cell's own genome (depending on the CRISPR-Cas subtype, when interference is inactivated, such spacers can constitute from 2 to 99% of acquired spacers [23,26,34,35]).…”
Section: Selection-based Methods Of Detection Of Crispr Adaptation Inmentioning
confidence: 99%
“…To analyze millions of CRISPR arrays in a single experiment, high-throughput sequencing (HTS) is usually used [38][39][40]. This allows one to study biases in spacer length, the distribution of corresponding protospacers along different DNA sources and their nucleotide composition [34,35,[38][39][40][41][42][43][44][45][46][47][48][49][50][51][52]. In principle, with sufficient sequencing depth, HTS of total genomic DNA purified from a culture should reveal reads corresponding to expanded arrays [53].…”
Section: Detection Of Crispr Adaptation In Cell Populationsmentioning
confidence: 99%
“…DSBs can be generated "accidentally" by missteps of information processing machineries, i.e., by mistiming of replication, replication-transcription complex conflicts, and replication or transcription through existing DNA damage/secondary structures [13][14][15][16]. DSBs are also purposefully generated as essential intermediates of many nucleic acid metabolism pathways [17][18][19][20] and if such pathways are aborted prematurely, intermediate complexes may be released inappropriately. Unchecked DSBs can be extremely detrimental to cellular health, causing arrests of replication and transcription which may lead to apoptosis.…”
Section: Double-strand Break (Dsb) Repairmentioning
confidence: 99%